Perkembangan Kognitif Anak Usia 5-6 Tahun Berdasarkan Keterampilan Berpikir Simbolik - hanifa, hanifahafiza; Karlina Sukma Wati; Dewi Safitri (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This article is a literature review that discusses the definition of cognitive development, AUD Cognitive Development According to STPPA Children Aged 5 to 6 Years, development in symbolic thinking, and indicators of achieving the development of symbolic thinking. In achieving a goal, this type of research is classified as descriptive which adopts a qualitative approach using library research methods. Cognitive development related to thinking skills, symbol recognition, and the creation of imaginary objects through the use of numeric and alphabetic symbols is known as symbolic cognition. Recognizing symbols made of numbers and letters is very important for a child's learning success. Because it is closely related to preparation for entering elementary school, where learning about reading, writing and arithmetic takes place. The aim of this journal to further enhance early childhood cognitive development in order to better prepare the next generation to lead with strong symbolic thinking skills and maximum intellectual potential.